Brain and muscle Arnt-like 1 is a key regulator of myogenesis - Chatterjee, Somik (The Company of Biologists, 2013)
The circadian clock network is an evolutionarily conserved mechanism that imparts temporal regulation to diverse biological processes. Brain and muscle Arnt-like 1 (Bmal1), an essential transcriptional activator of the clock, is highly expressed in skeletal muscle. However, whether this key clock component impacts myogenesis, a temporally regulated event that requires the sequential activation of myogenic regulatory factors, is not known. Here we report a novel function of Bmal1 in controlling myogenic differentiation through direct transcriptional activation of components of the canonical Wnt signaling cascade, a major inductive signal for embryonic and postnatal muscle growth. Genetic loss of Bmal1 in mice leads to reduced total muscle mass and Bmal1-deficient primary myoblasts exhibit significantly impaired myogenic differentiation accompanied by markedly blunted expression of key myogenic regulatory factors. Conversely, forced expression of Bmal1 enhances differentiation of C2C12 myoblasts. This cell-autonomous effect of Bmal1 is mediated by Wnt signaling as both expression and activity of Wnt components are markedly attenuated by inhibition of Bmal1, and activation of the Wnt pathway partially rescues the myogenic defect in Bmal1-deficient myoblasts. We further reveal direct association of Bmal1 with promoters of canonical Wnt pathway genes, and as a result of this transcriptional regulation, Wnt signaling components exhibit intrinsic circadian oscillation. Collectively, our study demonstrates that the core clock gene, Bmal1, is a positive regulator of myogenesis, which may represent a temporal regulatory mechanism to fine-tune myocyte differentiation.